2008
DOI: 10.1111/j.1469-7610.2007.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting deficits on executive functions between ADHD and reading disabled children

Abstract: Background: The object of this study was to analyze the executive functioning of children with attention deficit hyperactivity disorder (ADHD) or reading disability (RD) independent of their non-executive deficits. Methods: Three carefully diagnosed groups of children, aged between 7 and 12 years (35 ADHD, 22 RD and 30 typically developing children), were tested on a wide range of tasks related to five major domains of executive functioning (EF): inhibition, visual working memory, planning, cognitive flexibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
83
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 42 publications
13
83
1
7
Order By: Relevance
“…A number of studies have found that cognitive flexibility is impaired in children with ADHD [12][13][14][15]. However, other studies have failed to find impaired cognitive flexibility in children with ADHD [16,17].…”
Section: Child Development Researchmentioning
confidence: 94%
“…A number of studies have found that cognitive flexibility is impaired in children with ADHD [12][13][14][15]. However, other studies have failed to find impaired cognitive flexibility in children with ADHD [16,17].…”
Section: Child Development Researchmentioning
confidence: 94%
“…Thus caspase-3 deficiency "simulates" an ADHD-like behavior state, but it does not necessarily model all aspects of clinical ADHD, as typically presented. Indeed, ADHD is associated with, though not defined by, a broader range of cognitive impairments, including disrupted habituation, sensory modulation, and executive functions (Jansiewicz et al, 2004;Marzocchi et al, 2008;Ghanizadeh, 2011). Emerging literature suggests that multiple cognitive deficits associated with ADHD could be traced to impairment in fundamental selfregulatory mechanisms, including adaptive control (Shiels and Hawk, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…؊/؊ mice As reduced ability to adjust behavior in response to changed circumstances is commonly seen in certain neurodevelopmental disorders, including ADHD (Jurado and Rosselli, 2007;Marzocchi et al, 2008), we assessed behavioral flexibility of Casp3 Ϫ/Ϫ mice in spatial reversal learning in the Morris water maze (MWM) task. Mice were first trained to locate a submerged platform using distal spatial cues.…”
Section: Reduced Behavioral Flexibility In Casp3mentioning
confidence: 99%
“…The task was originally developed as a means of assessing planning, which Shallice (1982) argued was subject to selective impairment following lesions to the left frontal lobe. While some subsequent neuropsychological studies have failed to replicate the left frontal deficit reported by Shallice (e.g., Cockburn, 1995, but see Glosser & Goodglass, 1990, and Morris et al, 1997, the task remains popular as a tool for assessing executive functioning, particularly in clinical and neuropsychological populations (e.g., Donders & Larsen, 2012;Köstering et al, 2012;Marzocchi et al, 2008;Rainville, et al 2012; see Sullivan et al, 2009, for a meta-analysis) as well as in normally and atypically developing children and adolescents (e.g., Albert & Steinberg, 2011;Bull et al, 2004;Hartman et al, 2010;Kaller et al, 2008;Luciana et al, 2009). …”
Section: Introductionmentioning
confidence: 99%